Raw meat diets are a major risk factor for carriage of third-generation cephalosporin-resistant and multidrug-resistant E. coli by dogs in the UK - Morgan, Genever; Pinchbeck, Gina; Haldenby, Sam; Schmidt, Vanessa; Williams, Nicola (Frontiers in Microbiology, 2024)
Introduction: Raw-meat diets (RMD) for dogs, comprising unprocessed or non-heat-treated animal material, are increasingly popular. However, RMDs have been demonstrated to be contaminated with antimicrobial resistant (AMR) bacteria, and there is concern that such diets may pose a zoonotic disease risk. Additionally, dogs fed RMD may shed more AMRfaecal bacteria compared to those fed conventional cooked diets. Data from the UK remain limited; the present study investigated the presence of AMR-Escherichia coli in the faeces of RMD and non-RMD (NRMD)-fed dogs in the UK, the E. coli AMR gene complement, and the lifestyle risk factors associated with AMR-E. coli carriage.Methods: Faecal samples from UK-owned dogs (N=193 RMD, N=239 NRMD) and questionnaires discussing lifestyle factors, were obtained between October 2020-August 2021. Samples underwent culture and antimicrobial susceptibility testing to determine the presence of AMR-E. coli. Whole genome sequencing determined AMR gene carriage. Risk factors for the presence of AMR-E. coli were determined by multivariable modelling.Results: RMD dogs carried significantly more faecal AMR E. coli (p<0.001), including thirdgeneration cephalosporin resistant, extended-spectrum beta-lactamase (ESBL) producing, and multidrug resistant isolates and multivariable modelling confirmed raw-meat diets to be a significant risk factor. The blaCTX-M-15 gene was the most frequently identified blaESBL gene. The blaCTX-M-55 and blaSHV-66 genes were also prevalent and were only found in RMD dogs. The mobile colistin resistance gene, mcr-4 was identified in one ESBL-producing E. coli isolate from a NRMD-fed dog.Conclusions: This study has shown that dogs fed RMD in the UK are significantly more likely to shed E. coli which is resistant to highest priority critically important antibiotics, and multidrug resistant E. coli, than dogs fed NRMD. Additionally, AMR-E. coli isolates from RMD-fed dogs harbour multiple, diverse, and novel AMR genes. Therefore, provision of RMD to dogs could pose an important potential threat to human and animal health, especially given the close nature of the relationship many owners share with their pets. Awareness of these findings should be shared with pet owners, veterinary and medical professionals, pet food manufacturers and public health to mitigate potential risks.